2016
DOI: 10.1104/pp.16.00834
|View full text |Cite
|
Sign up to set email alerts
|

Primary Fatty Alcohols Are Major Components of Suberized Root Tissues of Arabidopsis in the Form of Alkyl Hydroxycinnamates

Abstract: Suberin is a complex hydrophobic polymer that acts as a barrier controlling water and solute fluxes and restricting pathogen infections. Suberin is deposited immediately outside of the plasmalemma in the cell wall of certain tissues such as endodermis of roots, aerial and underground periderms, and seed coats. Suberin consists of a variety of fatty acid derivatives polymerized with glycerol and phenolics. In this study, we show using liquid chromatography-tandem mass spectrometry and gas chromatography-mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…A suberin and cutin-like layer was recently described overlying developing LRP (51,52). Suberin and root cutin are composed from dicarboxylic acid (DCA), ω-hydroxy acids (ωOH), and fatty alcohols (OH) (52,53). The level of all C18-containing fatty acids typical of suberin/cutin (ωOH-18, 18-DCA, and 18-OH) was similar between puchi and WT (SI Appendix, Fig.…”
Section: Puchi and Vlcfas Control Pericycle Cell Proliferation On Callusmentioning
confidence: 78%
“…A suberin and cutin-like layer was recently described overlying developing LRP (51,52). Suberin and root cutin are composed from dicarboxylic acid (DCA), ω-hydroxy acids (ωOH), and fatty alcohols (OH) (52,53). The level of all C18-containing fatty acids typical of suberin/cutin (ωOH-18, 18-DCA, and 18-OH) was similar between puchi and WT (SI Appendix, Fig.…”
Section: Puchi and Vlcfas Control Pericycle Cell Proliferation On Callusmentioning
confidence: 78%
“…However, there was no significant increase in C20 primary alcohol levels, despite an increase in FAR4 transcript levels (Domergue et al ., ). Recently it has been shown that most esterified fatty alcohols are a major compound of suberin‐associated waxes (Delude et al ., ). Although, the suberin extraction method used here did not allow detection of associated waxes, upregulation of FAR5 indicated that the level of C20 primary alcohol could be increased in the associated waxes.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the suberin polymer is embedded with soluble lipids (unpolymerized aliphatics) called suberin-associated waxes (Vishwanath et al, 2015), which are considered to be the major contributors to the barrier against water diffusion across suberized cell walls (Soliday et al, 1979;. The waxes are solvent-extractable by brief (1-2 min) immersion of tissues in chloroform (Li et al, 2007;Molina et al, 2009;Kosma et al, 2012;Vishwanath et al, 2013) or by extensive solvent extraction of isolated periderms Serra et al, 2010;Delude et al, 2016). In Arabidopsis roots, some aliphatic waxes are suberin-associated and thus have characteristics common to some of the monomers released upon depolymerization of root suberin (Franke et al, 2006;Beisson et al, 2007).…”
Section: Suberin Chemical Compositionmentioning
confidence: 99%
“…These suberin-associated waxes include saturated fatty acids (commonly C16-C22), 18:0-22:0 fatty alcohols and alkyl hydroxycinnamate (AHC) esters (Li et al, 2007;Pollard et al, 2008). The AHC esters are comprised of phenylpropanoids, typically coumaric, ferulic, or caffeic acids, esterified to fatty alcohols, and up to 80% of the primary fatty alcohols in Arabidopsis roots exist in the form of AHC esters in suberin-associated waxes and alkyl caffeates are the predominant type (Kosma et al, 2012;Vishwanath et al, 2013;Delude et al, 2016).…”
Section: Suberin Chemical Compositionmentioning
confidence: 99%